Effects of a Furrow-Bed Seeding System on Stand Establishment, Soil Bacterial Diversity, and the Yield and Quality of Alfalfa Under Saline Condition - Sun, Juanjuan; Zhao, Jinmei; Zhang, Tengwei; Yu, Linqing; Jin, Ke (Frontiers in Plant Science, 2022)
Salt stress account for large decreases in crop yield all over the world. Furrow-bed system is an efficient practice to promote plant growth in soil salinity. However, the effects of Furrow-bed system on the soil environment and the growth of alfalfa (Medicago sativa L.) in salinity are not clear. For a wider and more detail evaluation, alfalfa were planted in fall in saline sandy loam soil, the effects of two plant systems (FU, furrow-bed seeding system; FL, flat-bed seeding system) on soil moisture, root-zone salinity, soil microbial community structure, seedling emergence number in the early stage of the growth period and soil nutrient contents, alfalfa production characteristics in the second growth year were determined in a two year field experiment. The result showed that, compared with FL, FU resulted in increased soil moisture content and seedling emergence, and significantly reduced relative abundance of Actinobacteria and Choroflexi in soil, but it did not affect root-zone salinity at the seedling stage. In April of second growth year, the soil salinity was lower, and the soil available phosphorus, potassium, nitrogen, and soil organic matter contents of the root-zone were higher in FU than in FL. Compared with FL, FU resulted in increased yield (by 37.5%), protein content (by 3.6%), and potassium concentration (by 33.2%,), and decreased ash content (by 7.7%) and sodium concentration (by 19.0%) in alfalfa plants. Pearson’s correlation analysis indicated that the increased yield was positively correlated with seedling emergence, soil available potassium, total nitrogen, and organic matter contents, and shoot potassium content; and negatively correlated with shoot sodium content. The relative abundance of Actinobacteria was negatively correlated with alfalfa ash, calcium, and sodium concentrations, and positively correlated with shoot potassium content. Taken together, the results indicate that Furrow-bed seeding in early fall alleviated salt stress of alfalfa and have the potential to enhance the yield and quality of alfalfa cultivated in saline soils by improving the soil environment and regulating the growth and physiology of alfalfa.